Trip wires and speed bumps : managing financial risks and reducing the potential for financial crises in developing economies - Grabel, Ilene (UN New YorkUS, 2004)
Investigates the shortcomings of the 'early warning systems' (EWS) that are currently being promoted in the multilateral and academic community. Advocates an integrated 'trip-wire-speed bump' regime to reduce financial risk and, as a consequence, to reduce the frequency and depth of financial crises in developing countries.